Synthesis, magnetic and spectroscopic studies of Ni(II), Cu(II), Zn(II) and Cd(II) complexes of a newly Schiff base derived from 5-bromo-2- hydroxybezylidene)-3,4,5-trihydroxybenzohydrazide) - Alhadi A.A.; Shaker S.A.; Yehye W.A.; Ali H.M.; Abdullah M.A. (2023)
A new hydrazide Shiff base ligand GHL1 (5-bromo-2-hydroxybezylidene)-3,4,5- trihydroxybenzohydrazide) was prepared by refluxing of trihydroxybenzhydrazide with an ethanolic of 5-bromo- 2-hydroxybenzaldehyde. The ligand reacted with Ni(II), Cu(II), Zn(II) and Cd(II) (acetate salts). All the complexes were characterized by elemental analysis, molar conductivity, TGA, UV-Vis and FT-IR spectral studies. All the complexes have octahedral geometry except Ni(II) complex which has tetrahedral geometry. 2012 Chemical Society of Ethiopia.